Long-Term Implications of Economic Complexity and Energy Intensity on the Environment in Lower-Middle-Income Countries in Asia - Wahyudi, Heru; Suripto, Suripto; Palupi, Widia Anggi (International Journal of Energy Economics and Policy, 2023)
This study aims to determine the long-term impact of Foreign Direct Investment (FDI), Population (POP), Economic Complexity Index (ECI), and Energy Intensity (EI) on environmental quality as measured by carbon dioxide (CO2). The objects of this research are lower-middle income countries in the Asian region during the 2000-2018 range. The method used in this research a is Fully Modified Ordinary Least Square (FMOLS). The results of this study indicate that FDI, population, economic complexity, and energy intensity increase the amount of CO2. These results produce policies related to the environment, where the government, the private sector, and the community have the same vision to improve the quality of the environment. The policy that can be taken is by setting strict regulations for investors so that the pollution haven hypothesis does not occur in lower-income countries in Asia. The policy was adopted by imposing a carbon tax. This policy is accompanied by reducing the birth rate, increasing innovation and economic complexity by paying attention to environmental sustainability, as well as carrying out energy transformation. Thus, it is expected to reduce the spread of CO2 that lower-middle-income countries are ready to become upper-middle-income countries or even high-income countries.